2017
DOI: 10.1590/1678-98652017000600011
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of unhealthy food habits and its association with socioeconomic factors among Brazilian workers

Abstract: A B S T R A C T ObjectiveInvestigate the clustering of four unhealthy food habits (low intake of fruits, low intake of vegetables, high intake of candy, and high intake of fried snacks), and to identify the association between the number of these clustered habits and sociodemographic variables. MethodsThis was a cross-sectional representative study of industrial workers from 24 Federative Units in Brazil conducted between 2006 and 2008. The low weekly intake of fruits and vegetables (<5 days/week) and high wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 13 publications
0
4
0
3
Order By: Relevance
“…More international studies focused on clustering adult population based on healthy eating or lifestyle. Benedet et al (2017) concentrated on unhealthy food habits and Anrdé et al categorized senior Norwegian citizens based on similarities of food consumption. This research focused on the healthy eating style of Hungarian adults.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…More international studies focused on clustering adult population based on healthy eating or lifestyle. Benedet et al (2017) concentrated on unhealthy food habits and Anrdé et al categorized senior Norwegian citizens based on similarities of food consumption. This research focused on the healthy eating style of Hungarian adults.…”
Section: Discussionmentioning
confidence: 99%
“…Among international researches more empirical results could be found that investigated a special consumer group (Tanton et al 2015;André et al 2017;Benedet et al 2017). Tanton et al (2015) analyzed the eating behavior of British university students whose lifestyle is considered to be risky when it comes about eating.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dietas com baixa variedade de alimentos e alto consumo de processados e ultraprocessados frequentemente estão associadas à ingestão deficiente de vitaminas hidrossolúveis, o que pode desencadear riscos à saúde de indivíduos de qualquer idade, bem como aumentar o risco de surgimentos de morbidades associadas (GABE, 2020;BENEDET et al, 2017).…”
Section: Introductionunclassified